MEDIA PEMBELAJARAN FLASH CARD DALAM PEMBELAJARAN UNDAK USUK BASA SUNDA DI KELAS 3 SEKOLAH DASAR - Riska Rosdiana; Dwi Alia; Erwin Saputra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to develop and evaluate the validity and practicality of flashcard-based instructional media to support the teaching of undak-usuk (levels ofpoliteness) in Sundanese language for third-grade elementary school students.The study employed the ADDIE development model, which consists of five stages:Analysis, Design, Development, Implementation, and Evaluation. The analysisstage revealed that many students struggled to differentiate between basa hormat(respectful language), loma (neutral language), and kasar (rude language) in dailyconversations. Furthermore, the existing instructional media used by teachersremained conventional and lacked contextual relevance, making it less engagingfor students.To address this issue, flashcard media were developed featuringillustrated everyday situations accompanied by example sentences using all threelevels of undak-usuk in Sundanese. Each card was designed with appealingvisuals and aligned with students’ local cultural contexts. The flashcards werevalidated by content and media experts, resulting in validation scores of 92.8%and 90.4%, respectively, both categorized as highly valid. Implementation trialswere conducted in two third-grade classes, showing very positive responses fromboth teachers and students. Teachers rated the practicality at 91.2% in Class III-Aand 94.5% in Class III-B. Student responses were also highly favorable, withpracticality scores of 87.5% in Class III-A and increasing to 95.6% in Class III-Bafter revisions. These results indicate that the flashcard media are highly valid,practical, and effective in helping students understand and apply undak-usuk inSundanese appropriately and contextually.